Teacher Communication Strategies In Teaching English At SMA Negeri 2 Poso - Pinky Christy Lubalu; Ika Paramitha Lantu (Universitas Sintuwu Maroso, 2025)
Abstract : The purpose of this research is to find out the communication strategies used by teacher in teaching Englishat SMAN 2 Poso. This research is a qualitative research that uses observation, interview and documentation to collectdata. The object of this research is one English teacher at this school that teaches English in 3 different classes. Thefindings show that the communication strategies used in teaching English is one-way communication and two-waycommunication, while the dominant one is two-way communication.